A new species of Batrachospermum, B. khaoluangensis Chankaew, Peerapornpisal et Kumano, sp. nov. (Batrachospermales, Rhodophyta) from Thailand - Wanninee Chankaew (2018)
In this study, Batrachospermum khaoluangensis Chankaew, Peerapornpisal et Kumano is described as a new species from Nakhon Si Thammarat Province, near Khao Luang National Park, southern part of Thailand. It is characterized by this unique suite of characters: carpogonium-bearing branches twisted; carpogonia more or less asymmetrical; trichogyne elongated-obconically or obovately or almost cylindrical, indistinctly or distinctly stalked: gonimoblast filaments loosely aggregated, radially branched, determinate filaments and defused indeterminate filaments creeping along cortical filaments: carposporangia spherical, egg-shaped, large, 10-14 μm in diameter, 16-20 μm long. According to phylogenetic data (unpublished) Batrachospermum khaoluangensis is far removed from genus Sirodotia, and the sections Contorta and Turfosa of genus Batrachospermum. This new species appeared to be close to species of Batrachospermum section Virescentia.